2009
DOI: 10.2807/ese.14.48.19425-en
|View full text |Cite
|
Sign up to set email alerts
|

Recently acquired HIV infection in men who have sex with men (MSM) in France, 2003-2008

Abstract: An increase in the number of new HIV diagnoses among men who have sex with men (MSM) was observed in several countries in the early 2000s. In this article, we explore the trends among MSM in France between 2003 and 2008. To estimate the number of MSM newly diagnosed with HIV, we take into account the reporting delay, underreporting and missing data for HIV case notification. To identify recent infections (RI) (acquired an average of six months before diagnosis), we used an enzyme immunoassay for recent HIV-1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
3
9
1
1
Order By: Relevance
“…This increase in the incidence of HIV seroconversions among men having sex with men is observed at the national scale in France [Semaille et al, ; Le Vu et al, ], in Europe [Likatavicius et al, ] and worldwide [Beyrer et al, ]. This high and increasing incidence is maintained despite the effects of antiretroviral therapy to decrease transmission at the population level [Montaner et al, ], due to multifactorial reasons: a higher transmission risk related to anal receptive intercourse (approximately 18 times higher than by vaginal intercourse) [Baggaley et al, ], high rates of partner changes, increase in unprotected anal sex and number of sexual partners, increase in HIV transmission in case of another concurrent sexually transmitted infections [Bouyssou et al, ], and missed opportunities for HIV testing [Champenois et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…This increase in the incidence of HIV seroconversions among men having sex with men is observed at the national scale in France [Semaille et al, ; Le Vu et al, ], in Europe [Likatavicius et al, ] and worldwide [Beyrer et al, ]. This high and increasing incidence is maintained despite the effects of antiretroviral therapy to decrease transmission at the population level [Montaner et al, ], due to multifactorial reasons: a higher transmission risk related to anal receptive intercourse (approximately 18 times higher than by vaginal intercourse) [Baggaley et al, ], high rates of partner changes, increase in unprotected anal sex and number of sexual partners, increase in HIV transmission in case of another concurrent sexually transmitted infections [Bouyssou et al, ], and missed opportunities for HIV testing [Champenois et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…These high rates are accompanied by rising incidence rates of HIV among MSM, as seen in the USA and France despite little change in overall population incidence [6•,7,8•,9]. A review of HIV incidence among MSM in the USA demonstrated an increase from 1.8 per 100 person-years in 1995 to 2.5 per 100 person-years in 2006 [10].…”
Section: The Prevalence and Incidence Of Hiv/aids Among Msmmentioning
confidence: 99%
“…Parten de una perspectiva etic, en tanto se privilegian las nociones del observador por sobre las de los observados. Si bien muchos de estos incluyen métodos cualitativos e incluso enfoques etnográficos, por lo general se trata de trabajos que privilegian una mirada objetivista sobre la sexualidad, lo cual se refleja en la denominación que alude a hombres homo/bisexuales y que ha servido de piedra de toque en sus investigaciones: "hombres que tienen sexo con hombres" (HSH) (Cáceres 2004;Fernández-Dávila et al 2008;Klavs et al 2009;Semaille 2009). Según Cáceres (2004: 40) este concepto "(1) correctamente alude a que es su conducta homosexual, y no su identidad sexual u otra asignación externa de «naturaleza homosexual» esencial, la que sirve para definir al grupo desde el punto de vista de la salud pública, en principio; (2) resulta un término inclusivo para muchos tipos de 'HSH' con distintas experiencias personales; y (3) se posiciona como una denominación técnica totalmente asimilable por los programas gubernamentales de lucha contra el SIDA".…”
Section: El Marco Analítico: Homosexuales Masculinos Y Estilos De Vidaunclassified